1999
DOI: 10.1111/j.1365-2621.1999.tb15105.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Firmness and Structure of Raw and Cooked Arrow Squid Mantle as Affected by Freshness

Abstract: Changes in firmness and structure of arrow squid (Loligo bleekert) mantle muscle during refrigeration (5°C) were studied. Shear force of raw mantle decreased sharply between 3 and 9 h refrigeration after killing. Light microscopic observations showed many pores between muscle cells in the softened raw samples. Transmission electron microscopic observations suggested that the spaces appeared as a result of detachment of muscle cells from connective tissues. After cooking the stored raw muscle, the shear force a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…Generally, seafood meat is considered to become softer with the reduction of freshness, and the cause of this phenomenon is reported to be due to the disintegration of collagen or connectin by endogenous proteinase in cool storage (Kugino et al, 1997;Ando et al, 1999;Kagawa et al, 2002). Since softening of the seafood meat was suppressed by using super chilling storage in the present study, disintegration of collagen and connectin might therefore be suppressed at the super chilling temperatures.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Generally, seafood meat is considered to become softer with the reduction of freshness, and the cause of this phenomenon is reported to be due to the disintegration of collagen or connectin by endogenous proteinase in cool storage (Kugino et al, 1997;Ando et al, 1999;Kagawa et al, 2002). Since softening of the seafood meat was suppressed by using super chilling storage in the present study, disintegration of collagen and connectin might therefore be suppressed at the super chilling temperatures.…”
Section: Resultsmentioning
confidence: 77%
“…Mizuta et al (1997) reported similar findings. In squid meat also, intercellular spaces appear when the meat becomes softer during cold storage (Ando et al, 1999). The reason for this phenomenon is thought to be the result of the intercellular connectivity becoming lower during cold storage.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the mean collagen diameter of RCGC was greater than that of RGC. High amounts of collagen lead to high hardness in raw fish muscle (Ando, Tsukamasa, Makinodan, & Miyoshi, 1999;Johnston, 1999;Johnston et al, 2000;Periago et al, 2005). This could be explained by the fact that high fiber density presents a higher surface-to-volume ratio in the muscle fibers, such that the connective tissue surrounding each fiber is relatively more abundant than in a muscle with low fiber density (Periago et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…2 There are several reports on the change in the freshness of squid during its storage. The indicators used were K -value, 3-5 texture [6][7][8][9] and taste. 10 In addition, squid has another practical freshness indicator: translucency of the muscle.…”
Section: Introductionmentioning
confidence: 99%